Role of the TNF-α receptor type 1 on prostate carcinogenesis in knockout mice - Galheigo, Maria Raquel Unterkircher; Cruz, Amanda Rodrigues; Cabral, Ágata Silva; Faria, Paulo Rogério; Cordeiro, Renato Simões; Silva, Marcelo José Barbosa; Tomiosso, Tatiana Carla; Gonçalves, Bianca Fachim [UNESP]; Pinto-Fochi, Maria Etelvina [UNESP]; Taboga, Sebastião Roberto [UNESP]; Góes, Rejane Maira [UNESP]; Ribeiro, Daniele Lisboa (Wiley, 2016)
BACKGROUND: TNF-α is a key cytokine involved in prostate carcinogenesis and is mediated by the TNF-α receptor type 1 (TNFR-1). This receptor triggers two opposite pathways: cell death or cell survival and presents a protective or stimulator role in cancer. Thus, the purpose of this study was to evaluate the role of TNF signaling in chemically induced prostate carcinogenesis in mice. METHODS: C57bl/6 wild type (WT) and p55 TNFR-1 knockout mice (KO) were treated with mineral oil (control) or N-methyl N-nitrosurea (MNU) in association with testosterone (MNU+T, single injection of 40 mg/kg and weekly injection 2 mg/kg, respectively) over the course of 6 months. After this induction period, prostate samples were processed for histological and biochemical analysis. RESULTS: MNU+T treatment led to the development of prostate intraepithelial neoplasia (PIN) and adenocarcinoma (PCa) in both WT and KO animals; however, the incidence of PCa was lower in KO group than in WT. Cell proliferation analysis showed that PCNA levels were significantly lower in the KO group, even after carcinogenesis induction. Furthermore, the prostate of KO animals had lower levels of p65 and p-mTOR after treatment with MNU+T than WT. There was also a decrease in prostate androgen receptor levels after induction of carcinogenesis in both KO and WT mice. Regarding the extracellular matrix in the prostate, KO mice had higher levels of fibronectin and lower levels of matrix metalloproteinase 2 (MMP2) after carcinogenesis. Finally, there was a similar increase in apoptosis in both groups after carcinogenesis, indicating that the TNAFr1 pathway in prostate carcinogenesis presented proliferative, and not apoptotic, stimuli. CONCLUSIONS: TNF-α, through its receptor TNFR-1, promoted cell proliferation and cell survival in prostate by activation of the AKT/mTOR and NFKB pathway, which stimulated prostate carcinogenesis in chemically induced mice. Prostate 76: 917–926, 2016. © 2016 Wiley Periodicals, Inc.
Keywords: AKT/mTOR; carcinogenesis; cell proliferation; prostate; TNF-α; TNFR-1